Transmission Cluster of Multiclass Highly Drug-Resistant HIV-1 Among 9 Men Who Have Sex With Men in Seattle/King County, WA, 2005−2007 - Buskin, Susan E. (2008)
BACKGROUND: From 2005 through 2007, Seattle health care providers identified cases of primary multiclass drug-resistant (MDR) HIV-1 with common patterns of resistance to antiretrovirals (ARVs). Through surveillance activities and genetic analysis, the local Health Department and the University of Washington identified phylogenetically linked cases among ARV treatment–naive and -experienced individuals. METHODS: HIV-1 pol nucleotide consensus sequences submitted to the University of Washington Clinical Virology Laboratory were assessed for phylogenetically related MDR HIV. Demographic and clinical data collected included HIV diagnosis date, ARV history, and laboratory results. RESULTS: Seven ARV-naive men had phylogenetically linked MDR strains with resistance to most ARVs; these were linked to 2 ARV-experienced men. All 9 men reported methamphetamine use and multiple anonymous male partners. Primary transmissions were diagnosed for more than a 2-year period, 2005−2007. Three, including the 2 ARV-experienced men, were prescribed ARVs. CONCLUSIONS: This cluster of 9 men with phylogenetically related highly drug-resistant MDR HIV strains and common risk factors but without reported direct epidemiologic links may have important implications to public health. This cluster demonstrates the importance of primary resistance testing and of collaboration between the public and private medical community in identifying MDR outbreaks. Public health interventions and surveillance are needed to reduce transmission of MDR HIV-1.